Determining seasonal dominant fish eggs and larvae species groups in the west of Tonkin Gulf - Pham Quoc, Huy; Nguyen Hoang, Minh (Vietnam Journal of Marine Science and Technology, 2021)
From 2003 to 2016, 1,649 samples were collected, covering both the time and space of the Gulf of Tonkin. The results have identified groups of seasonal dominant fish eggs and larvae: Seven species groups in Spring, nine species groups in the Summer, six species groups in Autumn, and four dominant species groups in the Winter. The dominant index (Yi) ranges from 0.02 to 0.26 depending on the species group and each season of the year, the highest in the Goby group - Gobiidae (Yi = 0.26) achieved in the Spring, followed by Herringgroup - Clupeidae reaches Yi = 0.20 in the Summer and the Anchovy group - Engraulidae reaches Yi = 0.16 in the Summer. The highest advantage index is only Yi = 0.09 in the Winter for Unicorn cod species - Bregmaceros macclelandi. During this period, the number of taxa and dominant indexes tended to decrease from Spring to Winter slightly.